Prosecuting and defending offences against children - Joyal, Lisa; Henderson, Lisa; Gibson, Jennifer; Cronin, Kasandra (Emond Montgomery Publications Limited, 2023)
"The second edition, written from the perspectives of defence, crown and judiciary, continues to be an essential guide to all offences involving physical abuse, sexual abuse, internet child exploitation (including child luring and child sexual abuse images), child neglect, and child death (including expert medical evidence issues pre- and post-Goudge that relate to the prosecution of such cases). The text explores the special accommodations available to children as witnesses, the assessment of children's evidence, and sentencing in child abuse cases. All chapters are being updated for new law and practice related developments, having particular regard for the inclusion of more case law from outside Ontario. The second edition includes two new chapters: one authored by Kasandra Cronin that deals with defending clients accused of offences against children, and one authored by Hospital for Sick Children forensic social workers Meredith Kirkland-Burke and Janeen Moddejonge on forensic social work, focusing on issues surrounding forensic interviewing protocols, child development, child memory, child trauma, and how crown, defence counsel, and judges can be more effective in their respective roles when dealing with child witnesses."– Provided by publisher
OCLC: 1372300510